Acceptability of an Opioid Relapse Prevention Text-message Intervention for Emergency Department Patients. Issue 6 (November 2017) - Suffoletto, Brian; Yanta, Joseph; Kurtz, Ryan; Cochran, Gerald; Douaihy, Antoine; Chung, Tammy
Abstract : Objective: To explore whether a text message-based relapse prevention intervention (Preventing and Interrupting Early Relapse [PIER]1) is acceptable to treatment-seeking adults with opioid use disorder (OUD) after Emergency Department (ED) discharge using mixed-methods design. Methods: Adults seeking care in an urban ED for OUD (n = 20; mean age 22; 55% female; 75% white race) completed a baseline survey, and were invited to enroll in PIER1, which was delivered in 7-day blocks, with the option to re-enroll at the end of each block, up to 4 blocks. PIER1 included a morning "push" message focused on positive thinking, adaptive coping feedback tailored to twice-daily assessments of craving severity and contextual correlates of craving, and end-of-day feedback on daily opioid use and goal commitment. Participants were asked to complete a follow-up phone interview after the first 7 days of PIER1. Transcripts were thematically coded. Results: Seventeen out of 20 participants enrolled in PIER1. In the first 7 days, response rates to text-message assessments averaged 30%. Ten out of 17 participants re-enrolled after 7 days. Main themes from follow-up interviews (n = 9) included ease of use, social connection, and self-empowerment. Participants desired more personalized support and the ability to communicate through text messaging with another person about their struggles. Event-level data suggest that higher craving severity increased risk of opioid lapses. Conclusions: In this mixed-methods intervention development study, we found conflicting evidence supporting an automated text-message intervention providing relapse prevention support for treatment-seeking individuals with OUD discharged from the ED. Qualitative feedback suggests that PIER1 could be useful and acceptability enhanced through personalized human support. Abstract : Supplemental Digital Content is available in the text